2012
DOI: 10.1254/jphs.12143fp
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Brain Oxidative Stress Model Induced by Microinjection of Sodium Nitroprusside in Mice

Abstract: Abstract. Sodium nitroprusside (SNP) is widely used as a potent vasodilator and a nitric oxide (NO) donor, whereas the cytotoxicity of SNP has been well documented. SNP releases several potentially toxic products such as cyanide anion, NO, and iron. We investigated the mechanisms of cell death and motor dysfunction induced by microinjection of SNP in mice to establish a brain oxidative stress model and then examined the anti-oxidant activity of glutathione. Intrastriatal microinjection of SNP (1 -10 nmol) indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
2
11
0
3
Order By: Relevance
“…It has been reported that SNP caused cell death dose-dependently when microinjected into the striatum. 23 In addition, cell death induced by intrastriatal microinjection of SNP was caused by iron-related ROS such as OH…”
Section: Autoradiographymentioning
confidence: 99%
“…It has been reported that SNP caused cell death dose-dependently when microinjected into the striatum. 23 In addition, cell death induced by intrastriatal microinjection of SNP was caused by iron-related ROS such as OH…”
Section: Autoradiographymentioning
confidence: 99%
“…We have previously established an in vivo brain oxidative stress model induced by intrastriatal microinjection of SNP (27), in order to evaluate the protective effects of antioxidant substances. In this study, using the oxidative stress model, we investigated the protective effect of luteolin against oxidative damage induced by SNPtoxicity.…”
Section: Protective Effect Of Luteolin On An Oxidative-stress Model Imentioning
confidence: 99%
“…We previously reported that iron-related radical reactions had crucial roles in SNP-induced brain damage (27). Thus, in order to elucidate the protective mechanism of luteolin, we used the DPPH method to determine Mice were orally administered luteolin (600 -1200 mg/kg) and after 24 h, SNP (10 nmol) was injected into the right striatum.…”
Section: Dpph Radical-scavenging Activitymentioning
confidence: 99%
“…DPPH Radical-Scavenging Activity We previously reported that iron-related radical reactions have crucial roles in SNP-induced brain damage. 25) Thus, to elucidate the protective mechanism of curcumin, we determined the free radicalscavenging activity of curcumin using DPPH. As shown in Fig.…”
Section: Effects Of Curcumin and Theracurmin Against Snp-induced Cytomentioning
confidence: 99%